Anthocyanin profiling of genetically diverse pigmented potato (Solanum tuberosum L.) clonal accessions from north-eastern sub-Himalayan plateau of India - Jammugani Vinod Kumar; Riman Saha Chowdhury; Prudveesh Kantamraju; Subir Dutta; Kumaresh Pal; Srinjoy Ghosh; Simanta Das; Rupsanatan Mandal; Suchand Datta; Ashok Choudhury; Somnath Mandal; Nandita Sahana (Heliyon, 2024)
White-fleshed potatoes have health concerns due to high glycemic index. Native and unexplored pigmented potato landraces may offer adequate and future smart alternatives with a balanced nutritional profile. Twenty-five pigmented potato clonal accessions across the eastern sub-Himalayan plateau of India were collected, purified and categorized into ‘Badami’ (UBAC) and ‘Deshi’ (UDAC) types. Evaluation of different nutritional attributes revealed that pigmented UBAC accessions are boosted with, high total dietary fibre, and total anthocyanin content and have remarkably low reducing sugar and glycemic index. Non-targeted LC-MS analysis identified caffeoyl and coumaroyl derivatives of delphinidin and petunidin glycosides, as major classes of anthocyanin compounds in pigmented potato accessions. HPLC-mediated quantification revealed high contents of delphinidin in the majority of accessions along with the selective presence of other anthocyanins. Selected accession was found to have polyphenolic compounds like gallic acid, vanillic acid, cinnamic acid and quercetin. The genetic cluster analysis of clonal accessions divided these genotypes into five major clusters. An ISSR repeat motif (AGG)6 was tightly linked with the total anthocyanin content of the accessions in Single Marker Analysis. Altogether, these native pigmented potato accessions offer a nutritious and healthy alternative to the conventional white-fleshed potato genotypes.